The effect of a low-energy high-current pulsed electron beam on surface layers of porous zirconium ceramics - Surzhikov V. P. Vladimir Petrovich; Frangulyan (Franguljyan) Т. S. Tamara Semenovna; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Vasil'ev I. P. (2014, 2014)
Title screen